Proposta de exoesqueleto para reabilitação de mão parética devido acidente vascular cerebral - Flório, Sérgio Henrique (2024)
Exoskeletons have been increasingly used as devices with the aim of assisting in the rehabilitation process for people who have suffered strokes and the consequences of hemiparesis. A known effective means of rehabilitation is the use of mirror neuron activation and it is expected that the use of an exoskeleton to use in this rehabilitation process will be able to maximize the results of the treatment. The work aims to contribute with a possible solution for hand rehabilitation exoskeletons that are functional and that meet the mirror neuron motor learning program. From a review of academic and market material, we understood the main characteristics that separate the types of exoskeleton configuration and analyzed which of them are requirements to meet the needs of the motor learning program. The project includes the development of a prototype based on the most prominent configuration, which was electromechanical with simple movement dynamics. A mechanical configuration of wire and pulley traction was chosen to extend the fingers and wrist, due to the anatomical characteristics of the human hand. Virtual and real prototyping is carried out, in addition to laboratory validation. In another study developed by Gisele Paiva, this exoskeleton is used to carry out tests on patients with hand hemiparesis.